Manajemen Pendidikan Karakter pada Ekstrakurikuler Pasukan Khusus : Studi Kasus di SMAN 1 Cerme Gresik - Alisya Maharani Putri Kastari; Sultoni Sultoni; Agus Timan; Imron Arifin (Global Leadership Organizational Research in Management, 2025)
Essentially, humans are equipped with their own individual characteristics from birth. However, over time, new traits will form and become the characteristics that are attached to each individual. The purpose of this study is to examine the character education program in the Pasukan Khusus Extracurricular at Senior High School 1 Cerme, the management process conducted, supporting factors and optimization activities, as well as the inhibiting factors and their solutions. The research method used is qualitative with a case study type. Data collection techniques include interviews, observation, and documentation. The data validity test used is credibility testing. The Pasukan Khusus Extracurricular at Senior High School 1 Cerme has five character education programs, namely: junior training (diklat junior), upgrading character, nationalism visits (kunjungan nasionalisme), attribute inspection (pemeriksaan atribut), and routine evaluations (evaluasi rutin). Pasukan Khusus Extracurricular at Senior High School 1 Cerme follows the stages of character education program management well, starting from planning, organizing, implementation, and supervision. Supporting factors include a high commitment from human resources, intensive communication between parties, support from the school, and a positive organizational culture. The optimization activities emphasize commitment and loyalty among members, full support for the program from the school, and the preservation of a good organizational culture. There are also inhibiting factors such as limited financial support, the time-consuming permission process from the school and parents, and some human resources who engage in deviations. The solutions to these problems include member contributions, sponsorships, minimizing the use of funds, submitting proposals well in advance of program implementation, and issuing warnings and sanctions to members who violate the rules.